2021
DOI: 10.2903/sp.efsa.2021.en-6460
|View full text |Cite
|
Sign up to set email alerts
|

Entomological survey to study the possible involvement of arthropod vectors in the transmission of African swine fever virus in Romania

Abstract: Mechanical transmission of African swine fever virus (ASFV) has been investigated on few occasions, with Stomoxys calcitrans experimentally shown to transmit ASFV which was detected in various body parts for 3 days after infection. However, up to date, there is no field evidence demonstrating the presence of viral DNA in blood-feeding arthropods. For this purpose, 30 pig farms from Romania where ASF was confirmed were selected for sampling according to a risk scoring system. In 9 farms, pigs were still present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 17 publications
0
15
0
1
Order By: Relevance
“…The Romanian data from the analysis of Stomatoxys and Culicoides collected from domestic pig outbreaks indicate a potential role of insects in spreading ASF [ 34 ]. However, the lack of a significant increase in ASF-positive wild boars in the summer season seems to exclude the role of insects in spreading the disease, at least in Poland.…”
Section: Discussionmentioning
confidence: 99%
“…The Romanian data from the analysis of Stomatoxys and Culicoides collected from domestic pig outbreaks indicate a potential role of insects in spreading ASF [ 34 ]. However, the lack of a significant increase in ASF-positive wild boars in the summer season seems to exclude the role of insects in spreading the disease, at least in Poland.…”
Section: Discussionmentioning
confidence: 99%
“…Ornithodoros erraticus occurs in localised areas of some Mediterranean countries [ 12 ], but ticks of this genus are neither native nor recently reported in the UK [ 13, 14 ]. Mechanical transmission by other insect and tick vectors has been postulated [ 15 ] and viral DNA was commonly detected in stable flies and biting midges on infected premises [ 16 ]. An infection route that bypasses mucosal barriers via biting arthropods is plausible, given the low infectious dose via this route [ 5 ].…”
Section: African Swine Fever Virus: the Role Of The Environmentmentioning
confidence: 99%
“…The predominant Obsoletus complex and Pulicaris complex were implicated in BTV transmission during the outbreak of bluetongue in northern Europe in 2006 [ 120 ], whereas Culicoides sonorensis was confirmed as a vector of EHDV in North America [ 121 ]. The role of Culicoides in ASFV transmission is also considered [ 122 ]. Although Akabane virus (AKAV) was initially isolated from mosquitoes, it has been reported that the main vectors for AKAV are the various Culicoides species [ 91 , 112 ].…”
Section: Main Arthropod Vectors Of Arbovirusesmentioning
confidence: 99%